Micheline Coulombe Saint-Marcoux et Marcelle Deschênes : pionnières dans le sentier de la création électroacoustique - Lefebvre, Marie-Thérèse (Circuit : musiques contemporaines, 2009)
A review of “masculine” and “feminine” attitudes towards music composition of the past fifty years highlights the contributions of Micheline Coulombe Saint-Marcoux and Marcelle Deschênes to the development of Québécois electroacoustic music. The author re-creates the historical context for the composers’ childhoods, adolescences, and periods of training in Montreal and Paris, and follows this with a discussion of how they negotiated the dominant trends of the 1970s. She then turns to the composers’ roles as pioneers: in their wish to depart from well-trodden paths, Coulombe Saint-Marcoux and Deschênes turned to new technological tools that would allow them to express a new artistic sensibility. From this perspective, they should be considered the “sherpas” of Québécois electroacoustic music.
Publisher: Les Presses de l'Université de Montréal

La semaine annuelle de musique de Montréal sous les auspices du Delphic Study Club, 1923–1937 - Lefebvre, Marie-Thérèse (Canadian University Music Review / Revue de musique des universités canadiennes, 2001)
This study begins with an examination of the background against which was founded the annual Music-Week in Montreal (1923–1937), then presents an analysis of its system of operation, inspired by the American model created in 1920 by Charles Milton Tremaine. Information on the staff of the association, its sponsors, financial grants, concert venues, performers, repertory, and lecturers is discussed; the main points of the press reviews of the events are extracted. The anglophone-francophone cultural dualism with regard to the conception of music and of its role in education emerges clearly in the conclusion, which also highlights the active role of women in the running of organizations destined to spread music in Quebec.
Publisher: Canadian University Music Society / Société de musique des universités canadiennes

Entretien avec Isabelle Panneton - Lefebvre, Marie-Thérèse (Les Cahiers de la Société québécoise de recherche en musique, 2011)
Sous forme d’entrevue, la compositrice se remémore les moments importants des cours d’analyse de Gilles Tremblay, plus particulièrement sa manière d’aborder le rapport de la poésie et de la musique, ainsi que son souci du traitement vocal, une approche qui se démarque par son caractère instinctif et sa vision organique des oeuvres. La compositrice parle également de sa propre approche de la poésie et présente quelques-uns de ses projets.
Publisher: Société québécoise de recherche en musique

Chronologie de plus de cent ans de présence féminine dans la création d'œuvres musicales au Québec : un premier survol - Lefebvre, Marie-Thérèse (Les Cahiers de la Société québécoise de recherche en musique, 2021)

La contribution des femmes à l’histoire musicale et les compositrices d’aujourd’hui au Québec - Lefebvre, Marie-Thérèse (L'accès des femmes à l'expression musicale. Apprentissage, création, interprétation. Les musiciennes dans la société contemporaine, 2005)